Nietzsche: ¿Political or Apolitical? - Gentili, Carlo (Estudios Nietzsche, 2012)
Although there is no proper political doctrine in Nietzsche, his thought certainly has a political dimension. Since the II Untimely Consideration on history Nietzsche appears to be taking a stance towards the situation of his time. Afterwards, in the very same concept of «will to power» society, ethics, physical world and political world are strictly connected. The concept of great politics has a central role, even if it has a primarily moral connotation. In general, one could say that the political sense of Nietzsche’s philosophy always derives from his moral ideas. He considers his personal destiny corresponding to Europe’s destiny. In his late works he deals with the concept of «aristocratic», which has to be understood as an aristocracy of the spirit rather than a social or political classification